Perfluoroalkyl Substance Serum Concentrations and Cholesterol Absorption-Inhibiting Medication Ezetimibe - Ge Ma; Alan Ducatman (Toxics, 2022)
Background: Per- and polyfluoroalkyl substances (PFAS) are human-made compounds with a widespread presence in human blood and other organs. PFAS have been associated with multiple health effects, including higher serum cholesterol and LDL cholesterol. Objective: Potential population differences in serum PFAS attributable to ezetimibe, a medication that inhibits cholesterol absorption, are of interest for several reasons. The “C8” Health Project survey data from six contaminated water districts in the mid-Ohio Valley of the United States provide a wide enough range of serum PFAS and a sufficient number of ezetimibe takers to explore this topic. Methods: A total of 44,126 adult participants of the C8 Health Survey were included in the community-based study. The status of taking (1075) or non-taking of ezetimibe, alone or in combination with another lipid-lowering agent, was acquired. The geometric mean serum concentrations of the four most commonly detected serum PFAS were compared based on the status of ezetimibe use. Results: There is no significant difference in serum concentrations of perfluorohexanesulfonic acid (PFHxS), perfluorooctanoic acid (PFOA), perfluorooctanesulfonic acid (PFOS), and perfluorononanoic acid (PFNA) between ezetimibe users and non-users after adjustment for age, sex, body mass index, estimated glomerular filtration rate (eGFR), cigarette smoking, education, and average household income. Conclusion: The sterol absorption-inhibiting medication ezetimibe does not appear to affect serum PFAS concentrations. We sought but did not find direct evidence that ezetimibe could inhibit PFAS uptake nor inferential evidence that inter-individual differences in sterol absorption could provide a confounding factor explanation for the association of serum total- and LDL-cholesterol with serum PFAS.